Leadership and Institutional Management in Education - Pohan, Muhammad Munawir; Anwar, Kasful; Shalahudin, Shalahudin (Continuous Education: Journal of Science and Research, 2024)
The objective of this study is to ascertain the management of leadership and institutions in education, specifically the Ministry of Religion, the Directorate of Islamic Religious Higher Education, and the Ministry of Education and Culture. The research methodology employed is library research. Primary data are sources that provide data directly from the first hand or are original sources. Secondary data are in the form of other books related to the problems that are the subject of discussion in this article. The steps of library research include: determining and formulating the problem or topic to be studied, collecting various written sources relevant to the research topic, and evaluating the relevance and credibility of each source after a significant literature review. The researcher then analyzes the content of the selected literature to identify patterns, themes, and trends relevant to the research topic. Finally, literature synthesis is achieved by combining information from various sources to form a more comprehensive understanding of the research topic. The results indicate that leadership management in educational institutions under the Ministry of Religious Affairs is a crucial element in the pursuit of educational excellence. Leadership management in the Directorate of Islamic Religious Higher Education (Diktis) is defined as the process of managing and organizing activities and resources in an effort to achieve the institution's strategic goals related to Islamic religious higher education in Indonesia. Leadership management at the Ministry of Education and Culture (Kemdikbud) is a process that involves the planning, organization, direction, and control of human and material resources in order to achieve national education goals.